Climate Prediction and Numerical Models - Stolz, Werner (2008)
The numerical prediction of weather and climate allows the estimation of the atmospheric scenarios for different time and spatial scales. The technology advances have contributed for temporal previsions periods much longer than some years ago. In Costa Rica, the high resolution numerical weather prediction started in the year 2003, been, actually, the fundamental tool for the weather forecast, both regional and local areas of the country, or for the estimation of the Climate Change scenarios in this century in the country.